Substitution and Solvent Effects on the UV Spectra of Chloro and Dichloranilines - Singh, S.N.; Prasad, R.K. (Asian Journal of Chemistry, 2010)
The UV spectroscopic studies of chloro- and dichloroanilines have been made. The shift in the primary and secondary bands have been examined in the light of Doub and Vandenbelt rule. The effect of substitution as well as the solvents have been explained in terms of electronic interaction within the molecules.